Food production potential and environmental sustainability of different integrated farming system models in northwest India - Fatima, Ayesha; Singh, Vinod Kumar; Babu, Subhash; Singh, Rajiv Kumar; Upadhyay, Pravin Kumar; Rathore, Sanjay Singh; Kumar, Basant; Hasanain, Mohammad; Parween, Hena (Frontiers in Sustainable Food Systems, 2023)
Accelerated energy use, negative environmental outcomes, and poor economic returns questioned the sustainability of contemporary agricultural production systems globally. The task is much more daunting in the northwest part of the India where natural resources dwindling are a major concern for sustainable agricultural planning. An integrated Farming system (IFS) encompasses various enterprises like crops, dairy, poultry, fisheries, etc can enhance farm productivity and environmental sustainability. Hence, the study hypothesized that the complementary interaction between the different enterprises will improve food production and reduce negative environmental outcomes. Therefore, production potential, and environmental sustainability of nine IFS models viz., crop enterprise (M2); crop + dairy (M3); crop + dairy + fishery (M4); crop + dairy + fishery + poultry (M5); crop + dairy + fishery + poultry + duckery (M6); crop + dairy + fishery + poultry + duckery + apiary (M7); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation (M8); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit (M9); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit + vermicompost (M10) was compared with the rice-wheat system (M1; business as usual). All the IFS models were tested during 2018-21. The highest food production (61. 5 Mg ha-1) was recorded under M10 but it remains statistically on par with M9. Concerning environmental sustainability, the combination of crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit + vermicompost (M10) recorded significantly higher energy output (517.6 × 103 MJ ha-1), net energy gain (488.5 × 103 MJha-1), energy ratio (17.8) and energy profitability (16.8 MJ INR-1) followed by M9. Furthermore, the M10 had the lowest greenhouse gas (GHG) intensity (0.164 kg CO2eq per kg food production). However, M9 had the highest eco-efficiency index (44.1 INR per kg GHG emission) followed by M10. Hence, an appropriate combination of diversified and complementary enterprises in an IFS model is a productive and environmentally robust approach for sustainable food production in the northwestern part of India.